The Relationships Between Blood Parameters of Liocarcinus depurator (Linnaeus, 1758) and Environmental Conditions in Çardak Lagoon (Çanakkale, Türkiye) - Hasan Ali KÜÇÜKBALLI (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2023)
In this study, the effects of environmental variables such as temperature, salinity, pH, and oxygen on blood variables of the portinid crab, Liocarcinus depurator, were determined. A total of 50 crabs were collected in Çardak Lagoon in 4 different periods; February, May, July, and November 2020. Crabs were first anesthetized on ice for 10 minutes and a 500 μL blood sample from each crab was collected from the coxae of the walking legs, using a 1 mL plastic syringe. The collected hemolymphs were then centrifuged and ELISA (Enzyme-Linked ImmunoSorbent Assay) analysis was performed. The effects of seasonal variables on blood variables were evaluated using Pearson’s correlation analysis. A negative relationship was found between temperature and ALB (albumin), while a negative relationship was found between saturated oxygen and GLU (glucose) and CHOL (cholesterol). The relationship between pH and CHOL was also negative.